Evaluation Of Stock Through Fundamental Analysis With The Dividend Discount Model (DDM) Approach - Lestari, Nurni Arrina; Antony, Antony; Alhidayatullah, Alhidayatullah (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
The goal of this research is to determine the fairness of stock prices by looking at the intrinsic value of shares in the healthcare industry from 2017 to 2021. Investors use this assessment of the fairness of the share price to choose whether to sell, hold, or purchase shares. The Dividend Discounted Model (DDM) with a Constant Growth Model was used for the analysis. The Dividend Discounted Model (DDM) is used to compare the stock's intrinsic value to its market value to determine the intrinsic value of shares. This value is calculated by anticipating future dividend payments. The Healthcare Sector Company on the Indonesia Stock Exchange is the subject of this kind of descriptive research. Nine companies were chosen as samples using the purposive sampling strategy. Shares of DVLA, KLBF, MERK, MIKA, PEHA, PRDA, SIDO, and TSPC were found to be undervalued in the outcomes. On the other hand, HEAL shares was found overvalued. For potential investors in DVLA, KLBF, MERK, MIKA, PEHA, PRDA, SIDO, and TSPC shares, the best investment decision is to buy shares in these companies before the market price of these shares rises. Meanwhile, investors who already own shares in these companies should hold the company's shares and increase their share ownership with the assumption that the share price will rise in the future. Furthermore, potential investors should not buy HEAL company shares and investors who already own the company shares should immediately sell the company shares in order to get capital gains.